Efektivitas Model Pembelajaran Terintegrasi Isu-Isu Lingkungan Berbasis Teknologi di Kota Pekalongan - Muhammad Ali Gunawan; Adib Muhammad; Efendy Supriadi (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2025)
This study aims to measure the effectiveness of an integrated environmental issue-based learning model using technology to enhance students' sensitivity and awareness in Pekalongan City, which faces various environmental challenges such as flooding and environmental degradation. The research was conducted at SDN Panjang Wetan, SMPN 2 Kota Pekalongan, and SMAN 4 Kota Pekalongan using purposive sampling. Data were collected through observations, interviews, and questionnaires administered to students and teachers. Data analysis employed descriptive statistics and t-tests to evaluate changes in students' understanding and involvement with environmental issues after the implementation of the technology-based learning model. The results indicate that the model is effective in enhancing students' sensitivity and awareness of environmental problems, as well as their skills in applying technology to environmental solutions. The contribution of this study is the introduction of an innovative learning approach that is relevant to the current needs of environmental education. The implication is that the implementation of this model can strengthen sustainable education and foster students' responsible behavior towards the environment at elementary to secondary school levels.